Teacher Capacity Management and Family Partnership for Early Childhood Nutrition via Local Fish Utilization - Eny Nur Aisyah; Fatchur Rohman; Heni Masruroh; Tuti Mutia; Alfi Sahrina; Choirul Anam; farizaika cahyani; Triata Mahendra Pesona Putra; Sandy Tegariyani Putri Santoso (Journal of Educational Management Research, 2026)
This study aims to examine how capacity management of Early Childhood Education (PAUD) educators and family partnership management can strengthen early childhood nutrition through the optimal utilization of local fish resources. A qualitative case study employed a Community-Based Participatory Action Research (CBPAR) approach involving 30 purposively selected informants, comprising 10 PAUD educators and 20 parents of children aged 4–6 years. Data were collected through participatory observation, in-depth interviews, and focus group discussions across four stages: needs analysis, nutrition education, tuna croquette-making training, and collaborative evaluation. Data were analyzed thematically and validated through triangulation. The findings indicate improved nutritional literacy, increased participant engagement in practical food processing, strengthened educator capacity as community nutrition change agents, and the development of sustainable family–school partnerships grounded in local wisdom. The tuna croquette product was perceived as nutritious, healthy, and appealing to young children, demonstrating the feasibility of integrating local food resources into child nutrition practices. The study contributes a context-responsive model linking educator capacity management, family partnerships, and local food optimization to early childhood nutrition improvement. Educational and local authorities should institutionalize local-food-based nutrition programs and strengthen multisectoral collaboration to support sustainable implementation and replication.